Brand Preference of PACKED MILK – Comparative Study on Rural and Urban Consumers in Ernakulam District - S.M, CHANDANRAJ; BINDU, K. JOTHI; Joseph, V. ALDRIN (International Journal of Psychosocial Rehabilitation, 2020)
Milk is one of the most important item consumed by the peoples in India. The packed milk is consumed by most of them. Brand preference of people may different in purchasing milk. So the study focused on the brand preference on packed milk in Ernakualm District. 400 samples were taken from 7 taluks of Ernakulam District and Garretts ranking method was applied for data analysis.